HUBUNGAN SELF REGULATION DENGAN PENYESUAIAN DIRI DALAM LINGKUNGAN KERJA PADA BINTARA REMAJA DI SAMAPTA POLDA JATENG - David Budi Ardi, Christian; Widyastuti, An Riwi (IMAGE, 2025)
This study aims to empirically examine the relationship between self-regulation and adjustment in the workplace among junior officers at Samapta Polda Jateng. The data collection methods included a workplace adjustment scale and a self-regulation scale. Purposive sampling was used to select 95 subjects. In this study, Spearman rho correlation analysis was conducted, revealing an rs value of 0.329 with a p-value of 0.0001 (p < 1%). These results indicate a significant positive relationship between self-regulation and workplace adjustment. The categorization of workplace adjustment levels was high at 85.3% and moderate at 14.7%. Meanwhile, the categorization of self-regulation levels was high at 74.7% and moderate at 25.3%. The self-regulation variable had a substantial impact on the workplace adjustment variable, accounting for 10.8%. Keywords: Workplace Adjustment, Self Regulation